CERTIFICATION AND SUPERVISION OF SHARIA CONFORMITY NATIONAL SHARIA COUNCIL INDONESIAN ULAMA COUNCIL (DSN-MUI) ON SHARIA PROPERTY - Mohammad Jamaludin (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2023)
AbstractThe usage of shariah labels in business activity, especially the property business, causes problems in some cities. This research was carried out to study the arrangement of certification law and the monitoring of shariah compliance in shariah property and the effort of DSN-MUI, The Representative of East Java Province, in certifying and monitoring shariah compliance in shariah property with a juridical empirical approach. The results of this research showed that the arrangement of certification law and monitoring of Shariah compliance in Shariah property is regulated in The Law of Limited Liability Company, The Law of Shariah Banking, and The Law of DSN-MUI Regulation. The effort done by DSN-MUI, The Representative of East Java Province, in certifying and monitoring the Shariah compliance in Shariah property was by explaining the principles of Shariah property normatively, recommending the discussion of Shariah property in The Leader Meeting of Central MUI, cooperating with BI, ADPS, and OJK to carry out training for The Prospective Shariah Supervisor, making education book and Jumat Preaching Book about Shariah Economy, and educating the community about DSN-MUI fatwa to improve the vigilance on fraud cases by using the Sharia label. Â Keywords: Sharia Certification; Monitoring of Sharia Compliance; Sharia Property.